Heavy Drinkers and the Potential Impact of Minimum Unit Pricing—No Single or Simple Effect?. (7th September 2017) - Gill, J; Black, H; Rush, R; O'May, F; Chick, J
Abstract: Aims: To explore the potential impact of a minimum unit price (MUP: 50 pence per UK unit) on the alcohol consumption of ill Scottish heavy drinkers. Methods: Participants were 639 patients attending alcohol treatment services or admitted to hospital with an alcohol-related condition. From their reported expenditure on alcohol in their index week, and assuming this remained unchanged, we estimated the impact of a MUP (50 ppu) on future consumption. (Around 15% purchased from both the more expensive on-sale outlets (hotels, pubs, bars) and from off-sales (shops and supermarkets). For them we estimated the change in consumption that might follow MUP if (i) they continued this proportion of 'on-sales' purchasing or (ii) their reported expenditure was moved entirely to off-sale purchasing (to maintain consumption levels)). Results: Around 69% of drinkers purchased exclusively off-sale alcohol at <50 ppu. Their drinking, post MUP, may reduce by a mean of 33%. For this group, from a population of very heavy, ill consumers, we were unable to show a differential effect across multiple deprivation quintiles. For other drinkers there might be no reduction, especially if after MUP there were many products priced close to 50 ppu. Moving away from on-sales purchases could support, for some, an increase in consumption. Conclusions: While a proportion of our harmed, heavy drinkers might be able to mitigate the impact of MUP by changing purchasing habits, the majority are predicted to reduce purchasing. This analysis, focusing specifically on harmed drinkers, adds a unique dimension to the evidence base informing current pricing policy. Short Summary: From drink purchasing data of heavy drinkers, we estimated the impact of legislating £0.50 minimum unit price. Over two thirds of drinkers, representing all multiple deprivation quintiles, were predicted to decrease alcohol purchasing; remainder, hypothetically, could maintain consumption. Our data address an important gap within the evidence base informing policy.